LLMonFHIR - Paul Schmiedmayer, PhD; Adrit Rao; Philipp Zagar, MS; Lauren Aalami, MS; Vishnu Ravi, MD; Aydin Zahedivash, MD, MBA; Dong-han Yao, MD; Arash Fereydooni, MD; Oliver Aalami, MD (JACC: Advances)
Background: To improve healthcare quality and empower patients, federal legislation requires nationwide interoperability of electronic health records (EHRs) through Fast Healthcare Interoperability Resources (FHIR) application programming interfaces. Nevertheless, key barriers to patient EHR access—limited functionality, English, and health literacy—persist, impeding equitable access to these benefits. Objectives: This study aimed to develop and evaluate a digital health solution to address barriers preventing patient engagement with personal health information, focusing on individuals managing chronic cardiovascular conditions. Methods: We present LLMonFHIR, an open-source mobile application that uses large language models (LLMs) to allow users to “interact” with their health records at any degree of complexity, in various languages, and with bidirectional text-to-speech functionality. In a pilot evaluation, physicians assessed LLMonFHIR responses to queries on 6 SyntheticMass FHIR patient datasets, rating accuracy, understandability, and relevance on a 5-point Likert scale. Results: A total of 210 LLMonFHIR responses were evaluated by physicians, receiving high median scores for accuracy (5/5), understandability (5/5), and relevance (5/5). Challenges summarizing health conditions and retrieving lab results were noted, with variability in responses and occasional omissions underscoring the need for precise preprocessing of data. Conclusions: LLMonFHIR's ability to generate responses in multiple languages and at varying levels of complexity, along with its bidirectional text-to-speech functionality, give it the potential to empower individuals with limited functionality, English, and health literacy to access the benefits of patient-accessible EHRs.